2013
DOI: 10.3141/2396-07
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Diversion Rate during Incidents on Basis of Main-Line Detector Data

Abstract: A number of intelligent transportation system technologies are deployed for disseminating information to travelers. One of the most important parameters for assessing the impacts and benefits of these deployments that influence route selection is the diversion rates of travelers. In this research, a method was developed to estimate traffic diversions on the basis of main-line detector data without the need for off-ramp detectors. In addition, the estimation allows the assessment of the guidelines and procedure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…These values are used in this study to modify the capacity distribution under normal (event-free) conditions. The impact of incidents on demand is also estimated by estimating the diversion rates during incidents using a relationship that estimates the average diversion rates during incidents for various combinations of total number of lanes and the number of blocked lanes, as developed by Hadi et al ( 39 ) based on data from the study area. As an example, for an incident which results in blockage of one lane out of four lanes, the utilized relationship estimates that the demand decreases by 11.07%.…”
Section: Methodsmentioning
confidence: 99%
“…These values are used in this study to modify the capacity distribution under normal (event-free) conditions. The impact of incidents on demand is also estimated by estimating the diversion rates during incidents using a relationship that estimates the average diversion rates during incidents for various combinations of total number of lanes and the number of blocked lanes, as developed by Hadi et al ( 39 ) based on data from the study area. As an example, for an incident which results in blockage of one lane out of four lanes, the utilized relationship estimates that the demand decreases by 11.07%.…”
Section: Methodsmentioning
confidence: 99%
“…The logit model estimates 21.3% and 21.4% diversions for short-term and long-term work zones, respectively. Hadi et al ( 18 ) conducted a study on the diversion of traffic in incident conditions based on detector data and found that the diversion rate ranges from about 8% for one out of five lane blockages to about 25% when four out of the five lanes were blocked.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Route diversion during incidents has been proven to be a useful tactic to mitigate non-recurrent congestion. Studies revealed that the diversion percentages are between 5% and 25% depending on the incident and traffic status ( 1–5 ). However, the anticipated congestion on the alternative routes discourages drivers from diverting, resulting in lower diversion percentages ( 6 ).…”
mentioning
confidence: 99%